ANALISIS PERKEMBANGAN TEKNOLOGI BERUPA ENTERPRISE RESOURCE PLANNING (ERP) TERHADAP PENINGKATAN KINERJA DAN PENGAMBILAN KEPUTUSAN EFEKTIF DALAM ORGANISASI - Muhammad Tofiq Effendi; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The development of information technology systems has undergone universal changes and transformations, significantly impacting business processes within organizations. One notable example is Enterprise Resource Planning (ERP), which has rapidly evolved and been widely adopted by various organizations. ERP is an integrated system used to manage business processes comprehensively within an organization. This study aims to explore and analyze how ERP implementation can enhance organizational performance and support more effective decision-making through a qualitative literature review approach. Data and theories were collected from various sources such as academic journals, scientific articles, and research reports discussing the relationship between ERP and organizational management. The analysis reveals that ERP usage improves operational efficiency, enhances data transparency, and strengthens coordination among units within the company. With real-time data integration, decision-makers obtain accurate and timely information, making the decision-making process more effective, efficient, and targeted. Additionally, ERP helps optimize resource utilization and reduce operational costs, positively impacting performance improvement and quality decision-making within the organization. However, the success of ERP implementation heavily depends on organizational readiness, top management support, and human resource capabilities. This study emphasizes the importance of strategic planning and effective change management to maximize the benefits of ERP implementation on organizational performance and decision-making.